A study on the impact of genetic polymorphisms of cytokines TNFα, IFNγ and IL10 in South Indian leprosy patients - Venkata Karunakar Kolla; Shehnaz Sultana; Samuel Abraham Joshi Davala; Vijaya Lakshmi Valluri (Wolters Kluwer Medknow Publications, 2021)
Background: Leprosy (Hansen's disease) is a chronic, debilitating disease predominantly of the peripheral nervous system characterized by the impairment of peripheral nerves and subsequent sensory loss caused by Mycobacterium leprae. The pro- and antiinflammatory cytokine genes play a major role in nerve damage in leprosy. Aims and Objectives: The objective of the present study is to ascertain the association of cytokine gene polymorphisms TNFα -308G/A (rs 1800629), IFNγ +874A/T (rs 2430561), and IL10 -1082G/A rs 1800896 in causation with leprosy. Materials and Methods: The present study comprised 365 leprosy patients and 185 control subjects. The polymorphisms in TNFα-308, IFNγ+874, and IL10-1082 genes were typed using the amplification refractory mutation system polymerase chain reaction method (ARMS PCR). Results: The present study found significant association between IL10-1082 GA heterozygote (P < 0.02) and IFNγ+874 AA (P < 0.001) genotype and leprosy. TNFα-308GA could not establish any association with the disease. Conclusion: The identification of genetic variations in pro- and antiinflammatory cytokines that are susceptible to leprosy would assist in better understanding of the pathogenesis of leprosy and perhaps lead to new approaches for diagnosis and treatment.